Pre- to postdiagnosis leisure-time physical activity and prognosis in postmenopausal breast cancer survivors - Jung, Audrey Y.; Schmidt, Martina; Benner, Axel; Steindorf, Karen; Chang-Claude, Jenny (Breast cancer research, 2019)
Physical activity (PA) before and after breast cancer diagnosis has been reported to be associated with lower mortality. However, whether changes in the activity after diagnosis impact prognosis is unclear and has not received much attention. This study aimed to examine pre- to postdiagnosis leisure-time PA and breast cancer prognosis.
Gesehen am 30.03.2020